1989
DOI: 10.1136/jcp.42.5.470
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of adenoid cystic carcinoma of the breast by immunohistology.

Abstract: SUMMARY An adenoid cystic carcinoma of the breast in a 78 year old woman was analysed immunohistologically for the production of type IV collagen, the expression of vimentin, epithelial membrane antigen (EMA) and steroid receptors, and the proliferative activity of the tumour cells. The data were compared with those obtained in eight adenoid cystic carcinomas of salivary glands and in ductal carcinomas of the breast with a cribriform growth pattern. The patients' ages were as follows: 45-80 years (mean 63 2) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…By classifying breast cell populations according to the system proposed by Bocker, 36 we identified four distinct types of cells in adenoid cystic carcinoma of the breast; rare CK5/6 þ cells (CK8/18À/p63À) or progenitor cells, CK5/6 þ /CK8/18 þ cells (/p63À) or glandular precursor cells, CK8/18 þ cells Although the origin of adenoid cystic carcinoma of the breast is still debated, it seems to be widely accepted that this tumor is derived from undifferentiated cells, which have the capacity to differentiate towards ductal and myoepithelial cells. 9,10,25,37 Our study confirmed this theory, as we demonstrated the presence of CK5/6 þ cells that could represent precursor cells. However, even by using a double immunostaining procedure, we were unable to identify a CK5/6 þ /P63 þ population of cells which could correspond to myoepithelial precursor cells.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…By classifying breast cell populations according to the system proposed by Bocker, 36 we identified four distinct types of cells in adenoid cystic carcinoma of the breast; rare CK5/6 þ cells (CK8/18À/p63À) or progenitor cells, CK5/6 þ /CK8/18 þ cells (/p63À) or glandular precursor cells, CK8/18 þ cells Although the origin of adenoid cystic carcinoma of the breast is still debated, it seems to be widely accepted that this tumor is derived from undifferentiated cells, which have the capacity to differentiate towards ductal and myoepithelial cells. 9,10,25,37 Our study confirmed this theory, as we demonstrated the presence of CK5/6 þ cells that could represent precursor cells. However, even by using a double immunostaining procedure, we were unable to identify a CK5/6 þ /P63 þ population of cells which could correspond to myoepithelial precursor cells.…”
Section: Discussionsupporting
confidence: 85%
“…Nonsentinel axillary lymph node dissection was performed in Adenoid cystic carcinoma of the breast S Azoulay et al eight cases. The median number of lymph nodes examined was 12 (range: [7][8][9][10][11][12][13][14][15][16][17][18][19]. No lymph node metastases were seen in either of these cases.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) but not the ductule-like structures [14]. EMA and high-molecular-weight keratin antibodies stain the larger cells lining the ductule-like structures [57], while these same antibodies are negative in the basaloid elements [14]. Immunohistochemistry with anti smooth muscle actin antibody reveals a third cell type.…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 99%
“…PAS staining and anti-collagen IV immunostaining reveal a thick basal lamina bordering the cribriform and the microcystic structures ( Fig. 3) but not the ductule-like structures [14]. EMA and high-molecular-weight keratin antibodies stain the larger cells lining the ductule-like structures [57], while these same antibodies are negative in the basaloid elements [14].…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 99%